Donation of surplus frozen pre-embryos to research in Israel: underlying motivations. Issue 1 (December 2016) - Raz, Aviad; Amer-Alshiek, Jonia; Goren-Margalit, Mor; Jacobi, Gal; Hochberg, Alyssa; Amit, Ami; Azem, Foad; Amir, Hadar
Abstract Background The high number of IVF procedures performed in Israel has had an unforeseen consequence: accumulation of large amounts of surplus frozen embryos. After five years that the frozen embryos are kept for free, patients need to make an embryo disposition decision. One option is donation for research. The donation rate in Israel is very low. Our aim was to understand the attitudes, values and perceptions of female IVF patients that decided to donate their surplus frozen embryos to research. Methods The study setting was a tertiary IVF unit which during the 2000–2009 period treated 241 patients who had their frozen pre-embryos stored for more than five years. The study population consists of the 12 patients (from among the 241) who had decided to donate their excess frozen pre-embryos to research. In-depth interviews were carried out with 8 of those 12 patients. Results IVF patients who donated their surplus frozen pre-embryos to research viewed the frozen embryo as a valuable resource that does not have human identity yet. The majority expressed a gradualist approach to the human status of the embryo as requiring successful implantation and development in the uterus. All the respondents chose donation to research not because it was their first choice but because they did not want or were unable to use the pre-embryos in the future, in addition to not willing to thaw them. For many of the respondents, donation to research was accompanied by a sense of uncertainty. All would have preferred to donate their pre-embryos to infertile women or couples, an option which is currently prohibited in Israel. Conclusions The moral reasoning behind decisions that patients make regarding excess pre-embryos is important for health care practitioners to consider when offering decision-making alternatives and counseling. For our respondents, the scarcity of donating excess frozen pre-embryos to research may reflect patients' preference for embryo donation to infertile couples. Recommended ways to increase donation to research may include public education and awareness, as well as targeted communication with IVF patients by multi-professional IVF unit teams comprised of a medical doctor and a professional trained in bioethics.